Influence of inlet configuration and distributor geometry on the performance of cryogenic plate-fin heat exchangers. (August 2021) - Haider, Patrick; Freko, Pascal; Acher, Thomas; Rehfeldt, Sebastian; Klein, Harald
Highlights: A three-dimensional simulation model is used to evaluate flow patterns in plate-fin heat exchangers. Performance of different distributor geometries is evaluated in terms of pressure drop and heat transfer. Different feasible inlet configurations of a 6-stream heat exchanger are compared to an idealized geometry. Inlet configurations can significantly affect the performance of plate-fin heat exchangers. Abstract: The influence of inlet placement and distributor geometry on the steady-state efficiency and pressure drop of cryogenic plate-fin heat exchangers (PFHEs) is studied using a three-dimensional simulation model. The simulation model employs a porous media approach to combine computational fluid dynamics with well-established correlations for heat transfer and pressure drop in fin materials. An isothermal study is conducted for comparison of six different distributor geometries. The selection of a favorable design depends on a trade-off between heat transfer and allowable pressure drop of a specific task but the presented results can serve as a guideline. Furthermore, two different configurations of a 6-stream PFHE are compared to an idealized, pseudo one-dimensional design. Both feasible designs lead to a significant increase in pressure drop and the thermal efficiency of the feasible designs differs by 5 percentage points. This highlights the necessity of considering the inlet- and distributor configuration in the design of a cryogenic PFHE.